Diversity of medium and large-size mammals from the Ejido Zomajapa Zongolica, Veracruz, Mexico: management implications - Mezhua- Velázquez, Mauricio Javier; Serna-Lagunes, Ricardo; Torres-Cantú, Gerardo B.; Pérez-Gracida, Luis David; Salazar-Ortiz, Juan; Mora-Collado, Norma (Ecosistemas y Recursos Agropecuarios, 2022)
The state of Veracruz is one of the greatest diversity of mammals in Mexico, so conducting studies in this group is a priority to assess its conservation status, given the accelerated transformation and loss of ecosystems. The objective of the study was to evaluate the taxonomic diversity of the community of medium and large mammals of the Ejido Zomajapa and its adjoining areas within the municipality of Zongolica, Veracruz. Between October 2019 and October 2020, through photo-trapping techniques, interviews with residents and transect searches, a richness of 27 species of mammals was recorded, distributed in 7 orders, 15 families and 24 genera. One species is critically endangered, one is considered threatened, and three species are near threatened. For the dry season a diversity of 25 effective species was estimated and for the rainy season it was 24 effective species, with no significant difference between them. The relative abundance of Dasyprocta mexicana stands out, endemic species of Mexico and with potential for use by managing its population. The presence of T. pecari through interviews is relevant, as it ́s a species considered extinct in the region. To conserve the richness and abundance of mammals recorded in this study, it is necessary to promote Units for the Conservation, Management and Sustainable Use of Wildlife (UMA) from a multidisciplinary perspective to promote the economic development of rural communities and minimize the anthropogenic impact on mammalian populations.